Commentary: The news media – the Prime Minister’s view - Helen Clark (Asia Pacific Network, 2008)
New Zealand has not always been the robust little democracy with the freedom of speech enjoyed today. The election of the first Labour government, the 1951 Waterfront Lockout emergency regulations and the Muldoon era were all testing times for the news media. In the first of the three commentaries, Prime Minister Helen Clark examines a politician’s view of media rights, responsibilities and ethics.